ISLAMISM IN ACEH: GENEALOGY, SHARI’ATIZATION, AND POLITICS - Alkaf, M; Abdullah, Irwan; Qodir, Zuly; Jubba, Hasse (Analisa: Journal of Social Science and Religion, 2022)
This paper argues Islamism in Aceh Province, Indonesia, has a long history within the social structure of the Acehnese people. Genealogically, there are two factors to view Islamism here, namely the relationship between Islam and politics in the past, and the people’s cultural and social construction, which has a strong Islamic base. Therefore, the collective memory about the relationship between Islam and politics, as well as the construction, then has implications in the lives of the Acehnese people in closely viewing those from various aspects. This study applies a qualitative method in which the data were collected through observation, interview, and documentation. The findings indicate that Islamism in Aceh is not a form of compensation from the Government of Indonesia to quell the conflict, but rather the form of aspirations that come from below on the long-standing awareness in the cultural and social structure of the locals regarding the relationship between religion and the state. In addition, unlike similar studies involving the notion of Pan-Islamism, the result shows that Islamism is more likely as the demands to retrieve political recognition.